FORMULATION AND EVALUATION OF FAST DISSOLVING ORAL FILMS OF FLUVASTATIN SODIUM BY USING TASTE MASKING TECHNIQUES - Upendra K Jain, Mandeep Kaur, Indu Bala, Anjoo Kamboj* (Journal of Biomedical and Pharmaceutical Research, 2016)
Fluvastatin sodium, a HMG-COA reductase inhibitor has shorter half life (1.2). It undergoes extensive first pass metabolism, frequent dosing is required in case of conventional dosage form. It is an bitter drug so an attempt was made to mask the taste by using three masking techniques. The present investigation indicates the possibility of developing Fluvastatin sodium loaded fast dissolving oral films to enhance the oral bioavailability by avoiding first pass metabolism to provide a rapid onset of action. Solvent casting method was used to formulate the fast dissolving oral film. Different formulation F1–F6 was prepared by using Artificial Sweetening Agents and Flavors (Sucrose, Saccharin); by using Viscosity Modification Method (CMC, Sucrose, Saccharin); by using β-cyclodextrin complexed drug Freeze Drying Method (Cyclodextrin, Sucrose, Saccharin). All the formulation were subjected to evaluation by various parameter like visual inspection, weight variation, folding endurance, film thickness, disintegration time, drug content, in vitro drug release, taste masking evaluation. Result obtained indicates all formulation F1-F6 were thin, smooth, flexible and uniform in drug content, weight and thickness as observed with low S.D. values. F6 be the best formulation from drug content, % release, taste masking effect and all other parameters. % release for F6 was found to be 99.6% within 150 sec (2.5 min) which falls within the limit as per pharmacopoeia (5-20 min) for oral dissolving films. Hence indicates quick onset of action within seconds as the oro mucosal absorption of the drug occurs directly from the site of administration to systemic circulation avoiding first pass metabolism to produce the desired action i.e offered significant results in terms of improving taste and bioavailability.Keywords: Fluvastatin sodium, Freeze Drying Method, taste masking techniques, in vitro drug release.